Investigation of Adenosine deamidase (ADA) activity and some biochemical values in lambs with infectious ecthyma symptoms - S. Kızıltepe; C. Okulmus; R. Akpınar; O. Merhan; K. Bozukluhan; N. Coşkun (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2025)
ABSTRACT Understanding the zoonotic risk posed by the orf virus (ORFV), which causes contagious ecthyma in domestic animals, is crucial for both human and animal health. Contagious ecthyma is a highly contagious, zoonotic, viral skin disease that affects sheep, goats, and certain other domestic and wild animals. In this study, serum malondialdehyde (MDA), nitric oxide (NO), reduced glutathione (GSH) concentrations, and adenosine deaminase (ADA) activity were measured in healthy and naturally infected lambs with ecthyma. Compared to healthy lambs, serum MDA (respectively; 2.69±0.4 vs. 4.73±0.24 μmol/L, P<0.001), NO (respectively; 6.12±0.72 vs. 8.32±0.55μmol/L, P<0.05) and ADA (respectively; 7.12±0.60 vs. 21.53±1.82 U/L, P<0.001) concentrations increased, while GSH (respectively; 15.01±1.59vs. 10.05±1.10mg/dL, P<0.05) levels decreased in contagious ecthyma lambs. As a result, it was concluded that oxidative stress developed in lambs infected with contagious ecthyma, ADA enzyme activity increased, and this could be useful for the diagnosis of the disease.